(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Depression is the most typical psychiatric issue among college students. The world’s mostpressing problem right now is depression. Every country spends a lot of money trying to treat psychiatricissues, depression included. According to a study of college students, 10 to 20 percent of the studentpopulation will have psychological issues . Therefore, such types of issues are putting a roadblock in thepath of overall progress. Students are particularly susceptible to the severe disease of depression,which has its roots in mental disorders. This study’s objective was to gauge the level of depressionamong college students.